(untitled) (Principles and Practice of Clinical Research, 2023)
Introduction: Acute respiratory distress syndrome (ARDS) is the leading cause of death among coronavirus disease 2019 (COVID-19) patients, mainly due to the cytokine storm and the rearrangements in coagulation and immune responses. Accordingly, the immunomodulatory and regenerative properties of umbilical mesenchymal stem cells (UC-MSCs) have been studied for the treatment of COVID-19. Methods: This mini-review evaluated adults with moderate-severe COVID-19 infection and compared the results of placebo plus standard of care (SOC) therapy with those obtained from the administration of umbilical cord mesenchymal cells (UC-MSCs). We searched the following databases: Cochrane, Central Register of Controlled Trials, and PubMed; subsequently, 8 clinical trials were included in this mini-review. Some statistically significant difference was found in the levels of clinical and inflammatory markers between the intervention and the control groups. Conclusion: Early phase trials have shown the promising efficacy and safety of UC-MSC therapy for COVID-19-associated moderate-to-severe ARDS. Large multicenter phase III randomized controlled clinical trials will further confirm these findings.